Nomenclatural notes on some Diptera genus-group names of P.A. Latreille - Evenhuis, Neal L. (Zootaxa, 2012)
Nomenclatural notes are presented for a few Diptera genus-group names of P.A. Latreille. Gonypes Latreille [Asilidae] is foundto be available from 1804 and not 1805 with no change in type species designation. Molobrus Latreille [Sciaridae] is found tobe available from 1804 and not 1805, and its type species, Tipula thomae Linnaeus, 1767 is fixed by invoking Article 70.3 ofthe ICZN Code, which maintains its junior synonymy under Sciara Meigen, 1803. Oligotrophus Latreille [Cecidomyiidae] isfound to be available from 1804 and not 1805 with no change in type species designation. The earliest valid subsequent typedesignation from originally included species was found for Pangonius Latreille [Tabanidae] to be Tabanus proboscideusFabricius, 1794 by Ersch & Gruber in 1838. Voluccella Fabricius, 1794 is deemed to be an available name (not an incorrectsubsequent spelling of Volucella Geoffroy, 1762) and thus has priority over Usia Latreille, 1802. In order to maintain stabilityof nomenclature and prevailing usage, reversal of precedence is invoked (ICZN Code Article 23.9.2) and Usia Latreille is conserved as a nomen protectum and Voluccella Fabricius, 1794 is treated as a nomen oblitum.